Additives for Spark Ignition and Compression Ignition engine fuels. (January 2018) - Bennett, John
Fuel additives for automotive applications have been in use for almost as long as the automobile has existed. They provide significant benefits, both in making fuels fit for purpose and to deliver protection and performance benefits. Performance benefits can range from protection against degradation, through recovery of lost performance, all the way to enhanced engine function. This has become particularly important with the tension between increasingly stringent long emissions requirements, the encouragement of renewable biofuel content and the drive to improved engine efficiency and reduce fuel consumption. The paper discusses where performance fuel additives provide their benefits and how they are evolving to work with latest generations of fuel and engines, and provides an overview of the current and upcoming industry engine tests for fuels and their additives.